Early dentine erosion assessment with noninvasive method / Madiha Habib - Madiha, Habib (2018)
Non-invasive assessment of early dentine erosion is required for clinical validation of therapeutic strategies aiming to reduce or arrest the progression of this condition. The purpose of this thesis was to seek a non-invasive method suitable for monitoring early dentine erosion progression with the ultimate goal of using this tool in clinical trials involving dentine erosion. To achieve this purpose, this thesis aimed to first assess the potential of optical coherence tomography (OCT) for monitoring early dentine erosion progression, second, to assess the potential of surface roughness as a method for measuring early dentine erosion progression in simulated intraoral conditions and finally to assess if OCT is a sensitive tool to detect early dentine erosion and monitor its progression in simulated intraoral conditions by correlating OCT data with surface roughness data. Root dentine samples were first immersed in 0.3% citric acid for a total of 30 minutes. Measurements with OCT and field-emission scanning electron microscopy (FE-SEM) were obtained at varying erosion intervals. Integrated OCT intensity changes were compared with FE-SEM observations. Next, root dentine samples were subjected to a cycling erosion challenge with 0.3% citric acid for 10 minutes, three times a day interspersed with periods of simulated salivary remineralisation for three days. Measurements with OCT and non-contact profilometry were obtained on every cycling day. Fractional change of average roughness and bearing curve parameters was compared with fractional change of surface loss and FESEM observations. Finally, fractional change of integrated OCT intensity was compared with fractional change of roughness parameters and FE-SEM observations. Integrated OCT intensity was able to monitor the progression of early dentine erosion for 30 iv minutes with a detection threshold of two minutes from baseline. Mean percentage change in integrated OCT intensity exhibited linear pattern (R2 = .99) with erosion interval. Integrated OCT intensity changes corresponded with FE-SEM observations. Average roughness (fRa1) and bearing curve parameters namely core roughness (fRk), peak roughness (fRpk) and valley roughness (fRvk) were able to longitudinally measure the progression of early dentine erosion as opposed to fractional change of surface loss.FE-SEM images supported the surface roughness results. Integrated OCT intensity was able to longitudinally measure early dentine erosion for three days in simulated intraoral conditions with a detection threshold of day one from baseline measurement. Fractional change of integrated OCT intensity correlated moderately but significantly with fRk and fRa1 (r = .428 and .394 respectively) and showed a weak but significant correlation with fRpk and fRvk (r = .300 and .217 respectively). Integrated OCT intensity changes corresponded with ultrastructural changes of early eroded dentine. These studies suggested that OCT and surface roughness parameters are suited for monitoring the progression of in vitro early dentine erosion non-invasively and could be possible tools for monitoring early dentine erosion progression in clinical trials.